Realizacja kryteriów konwergencji z Maastricht przez kraje Unii Europejskiej - Kowalik, Paweł (The Realization of the Criteria of Convergation from Maastricht by the European Union States, 2008)
The euro is the currency of thirteen European Union countries (namely Belgium, Germany, Greece, Spain, France, Ireland, Italy, Luxemburg, the Netherlands, Austria, Portugal, Slovenia, and Finland). This article is on monetary integration in the European Union. The aim of the paper is to present current situation of the states which belong to Economic and Monetary Union in fulfilling the criteria of convergation and to answer the question if the other member states are ready to fulfill them.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 300-312